2021
DOI: 10.1136/bmjopen-2021-050223
|View full text |Cite
|
Sign up to set email alerts
|

Beyond PPE: a mixed qualitative–quantitative study capturing the wider issues affecting doctors’ well-being during the COVID-19 pandemic

Abstract: The COVID-19 pandemic has brought unprecedented challenges to the medical workforce. This has put them at increased risk of burnout at a time when levels are already worryingly high in the profession, with recent studies consistently showing that around half of doctors meet the validated criteria for burnout.ObjectivesTo understand the wider factors influencing and impacting upon hospital doctors’ well-being during the COVID-19 pandemic in England.DesignCross-sectional survey and mixed quantitative–qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 39 publications
3
53
0
2
Order By: Relevance
“…The current study result is in concordance with recent studies of healthcare workers in German or Italy during COVID-19 that showed associations between working at COVID-19 frontline versus higher level of perceived stress or post-traumatic symptoms [ 44 , 49 ]. Further, other studies that examined mental health of medical professionals at frontline of COVID-19 pandemic also demonstrated increased odds of mental health worsening (depressive mood, anxiety, or burnout) in presence of working environments such as insufficient supply of personal protective equipment [ 50 54 ], endorsed barriers at working [ 55 ], increased physical and psychological workload [ 51 , 56 , 57 ], reduced amount of day-off and successive period of active duty after 24-h shifts [ 50 ]. Collectively, sufficient and timely supply of personal protective equipment and efficient distribution of rest period between the active duty are required for protection of mental health for PHDs at frontline of pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The current study result is in concordance with recent studies of healthcare workers in German or Italy during COVID-19 that showed associations between working at COVID-19 frontline versus higher level of perceived stress or post-traumatic symptoms [ 44 , 49 ]. Further, other studies that examined mental health of medical professionals at frontline of COVID-19 pandemic also demonstrated increased odds of mental health worsening (depressive mood, anxiety, or burnout) in presence of working environments such as insufficient supply of personal protective equipment [ 50 54 ], endorsed barriers at working [ 55 ], increased physical and psychological workload [ 51 , 56 , 57 ], reduced amount of day-off and successive period of active duty after 24-h shifts [ 50 ]. Collectively, sufficient and timely supply of personal protective equipment and efficient distribution of rest period between the active duty are required for protection of mental health for PHDs at frontline of pandemic.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Cubitt et al identified a decline in mental health common to all medical specialties, however, less expressed in those who worked in acute care medicine. 32 Habit in managing complex situations may in fact mitigate the effect of the pandemic on physicians' mental health. Similarly, it is conceivable that the broader scope of work of the internists in our hospital that work in inpatient unit, rather than outpatient settings, and manage patients with more comorbidities (as the ones with coronavirus disease usually show), could make physicians board‐certified in internal medicine less vulnerable to burnout and stress when managing this type of patient.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2020, the COVID-19 pandemic has affected approximately 150 million people and taken over 3 million lives [ 6 ]. Furthermore, it has posed an unprecedented challenge to the healthcare profession worldwide and increased the existing risk of burnout for doctors [ 7 ]. Similar to studies conducted in China and Italy, the BMA reported that more than 50% of doctors have had progressive worsening of general health and well-being since the first wave [ 8 ].…”
Section: Introductionmentioning
confidence: 99%